The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.tipsro.2020.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Quality management in radiation therapy: A 15 year review of incident reporting in two integrated cancer centres

Abstract: a b s t r a c tFifteen years of reported incidents were reviewed to provide insight into the effectiveness of an Incident Learning System (ISL). The actual error rate over the 15 years was 1.3 reported errors per 1000 treatment attendances. Incidents were reviewed using a Mann-Whitney U Test. The average number of incidents per year and the number of incidents per thousand attendances declined over time. Two seven-year periods were considered for analysis and the average for the first period (2005-2011) was 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
(24 reference statements)
2
10
0
Order By: Relevance
“…Bissonnette and Medlam 7 found that increases in treatment complexity resulted in increases in documentation errors, which aligns with the findings of the current study. Smith et al 20 also reported on a fifteen-year review of incident data in 2020, reporting similar results to the current study with regards to increases in near misses and errors related to the implementation of new technology. Their study found an increase in near miss events associated with the 20 However, overall, there is a paucity of literature reporting a comparative analysis of radiation incidents in relation to the implementation of new technology and electronic processes plus changes within a large academic department over a greater than a ten-year period.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Bissonnette and Medlam 7 found that increases in treatment complexity resulted in increases in documentation errors, which aligns with the findings of the current study. Smith et al 20 also reported on a fifteen-year review of incident data in 2020, reporting similar results to the current study with regards to increases in near misses and errors related to the implementation of new technology. Their study found an increase in near miss events associated with the 20 However, overall, there is a paucity of literature reporting a comparative analysis of radiation incidents in relation to the implementation of new technology and electronic processes plus changes within a large academic department over a greater than a ten-year period.…”
Section: Discussionsupporting
confidence: 87%
“…Smith et al. 20 also reported on a fifteen‐year review of incident data in 2020, reporting similar results to the current study with regards to increases in near misses and errors related to the implementation of new technology. Their study found an increase in near miss events associated with the introduction of image‐guided RT (IGRT) technology.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations